The Antioxidants in Prevention of Cataracts Study: effects of antioxidant supplements on cataract progression in South India. Issue 7 (23rd March 2006) - Gritz, D C; Srinivasan, M; Smith, S D; Kim, U; Lietman, T M; Wilkins, J H; Priyadharshini, B; John, R K; Aravind, S; Prajna, N V; Duraisami Thulasiraj, R; Whitcher, J P
Abstract : Aim: To determine if antioxidant supplements (β carotene and vitamins C and E) can decrease the progression of cataract in rural South India. Methods: The Antioxidants in Prevention of Cataracts (APC) Study was a 5 year, randomised, triple masked, placebo controlled, field based clinical trial to assess the ability of interventional antioxidant supplements to slow cataract progression. The primary outcome variable was change in nuclear opalescence over time. Secondary outcome variables were cortical and posterior subcapsular opacities and nuclear colour changes; best corrected visual acuity change; myopic shift; and failure of treatment. Annual examinations were performed for each subject by three examiners, in a masked fashion. Multivariate modelling using a general estimating equation was used for analysis of results, correcting for multiple measurements over time. Results: Initial enrolment was 798 subjects. Treatment groups were comparable at baseline. There was high compliance with follow up and study medications. There was progression in cataracts. There was no significant difference between placebo and active treatment groups for either the primary or secondary outcome variables. Conclusion: Antioxidant supplementation with β carotene, vitamins C and E did not affect cataract progression in a population with a high prevalence of cataract whose diet is generally deficient in antioxidants.